Sistem Informasi Geografis Lahan Pertanian Pangan Berkelanjutan Pada Dinas Tanaman Pangan, Hortikultura Dan Peternakan Kabupaten Muara Enim - Agrios Kanny; K. Ghazali K. Ghazali; Evi Yulianti (Jurnal Informatika Global)
The Geographic Information System (GIS) for Sustainable Food Agriculture (LP2B) is an information system application that functions to produce accurate, relevant and accountable data and information which will later be used as a basis for planning, stipulating, utilizing, evaluating and controlling the area and land and sustainable food agriculture reserve land that can be accessed by the community and stakeholders. This study uses data collection methods in the form of literature studies, field studies (interviews and observations) and literature studies as a method of approach in data collection. In this study using a system development method using Rapid Application Development (RAD) method, where there are three phases of development, namely the phase of Requirement Planning, Workshop Design and Implementation. In the geographic information system of sustainable agricultural land use web gis based PHP programming using javascript leaflets as the implementation of the projected map of the earth on the geographic information system of sustainable agricultural land. The results of this study can later be used as a reference for the Muara Enim District Government through the Muara Enim Regency Food Crops, Horticulture and Livestock Service Office in making decisions on which paddy fields will be used as Sustainable Food Agriculture Land, and are expected to continue to appeal to and pay attention to farmers LP2B so that paddy fields in Muara Enim Regency can avoid land conversion or reduced paddy fields that will threaten food security. Keywords : Geographic Information System, Muara Enim Regency, Land of Sustainable Food Agriculture.